Effect of W–Mo balance on long-term creep life of 9Cr steel. (4th July 2019) - Abe, Fujio; Ohba, Toshio; Miyazaki, Hideko; Toda, Yoshiaki; Tabuchi, Masaaki
ABSTRACT: The effect of tungsten–molybdenum (W–Mo) balance on creep life has been investigated for five heats of martensitic 9Cr steel with 1.5 % Mo equivalent (= 1/2W + Mo) at 600, 650 and 700°C. The combination of W and Mo concentrations in the present steel is 3W–0Mo, 2.8W–0.1Mo, 2.4W–0.3Mo, 1.8W–0.6Mo and 0W–1.5Mo. The time to rupture t r exhibits a monotonous increase with increasing the W–Mo balance parameter 1/2W/(1/2W + Mo), namely, with increasing W concentration and concomitantly with decreasing Mo. The increase in t r with increasing 1/2W/(1/2W + Mo) becomes less significant at long times. The precipitation of Fe2 (W, Mo) Laves phase takes place preferentially at prior austenite grain boundaries during creep, which enhances the grain boundary (GB) precipitation hardening. The amount of Laves phase increases with increasing 1/2W/(1/2W + Mo). The coarsening of Laves phase takes place at long times during creep, which reduces the GB precipitation hardening.